Development of a Divergent Route to Erythrina Alkaloids - Clementson, Sebastian; Jessing, Mikkel; Vital, Paulo J.; Kristensen, Jesper L. (Synlett, 2020)
Erythrina alkaloids were identified at the end of the 19th century and today, more than 100 members of the erythrinane family have been isolated. They are characterized by a unique tetracyclic, α-tertiary spiroamine scaffold. Herein we detail our efforts towards the development of a divergent enantioselective synthesis of (+)-dihydro-β-erythroidine (DHβE) – one of the most prominent members of this intriguing family of natural products.1 Introduction2 Synthetic Strategy2.1 First Generation2.2 Second Generation2.3 Third Generation2.3.1 Radical Endgame2.3.2 Completion of the Total Synthesis3 Conclusion
Keywords: Erythrina alkaloids; total synthesis; asymmetric allylic alkylation; ring closing metathesis; decarboxylative cross coupling; spiroamine